A microchip for exosome isolation that can be impregnated with imatinib simultaneously: an in vitro analysis - Amir Monfaredan; Fakher Rahim; Gholamreza Tavoosidana; Mohammad Hossein Modarressi; Alaviyehsadat Hosseininasab; Ali-Akbar Aghajani-Afrouzi; Mahdi Shafiee Sabet; Elahe Motevaseli (Russian Open Medical Journal)
Background and Aims — Exosomes, which are tiny double-layered membranes originating from eukaryotic cells, have been recognized as a valuable natural vehicle for delivering substances because of their optimal size, compatibility with living organisms, strong structure, ability to carry a large amount of cargo, and capacity to be modified on their surface. Methods — Various strategies have been employed to isolate exosomes due to the challenges associated with maintaining their high purity. The current investigation utilized a soft lithography technique to fabricate channels for exosome separation, incorporating immunoaffinity capabilities. Both biochemical and biophysical assays were conducted to assess the quality of isolated exosomes from various sources (serum, cell supernatant, and urine) and compared with a commercially available kit. Results — The current investigation employed a microfluidic method to capture CD63-conjugated magnetic beads, resulting in a very effective separation of exosomes. Based on the data, there were no notable variations in miRNAs that were statistically significant. This demonstrates that the engineered chip successfully achieved the separation of the exosome while preserving the integrity of its nucleic acid components. Conclusion — The results shown that the current methodology effectively isolated exosomes with a high yield rate, purity, and minimal time requirement. The imatinib laden exosomes demonstrated anticancer efficacy against the KYO-1 cell line in all of their forms.